2022
DOI: 10.3390/atmos13010089
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Hydrological Events and Temporal Trends in CAPE and TCWV over the Main Cities Facing the Mediterranean Sea in the Period 1979–2018

Abstract: The Mediterranean region is regarded as the meeting point between Europe, Africa and the Middle East. Due to favourable climatic conditions, many civilizations have flourished here. Approximately, about half a billion people live in the Mediterranean region, which provides a key passage for trading between Europe and Asia. Belonging to the middle latitude zone, this region experiences high meteorological variability that is mostly induced by contrasting hot and cold air masses that generally come from the west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The meteo-climatic features of this area are linked to the cyclogenesis of the Gulf of Genoa [36], which causes events of short but intense precipitation (less than 6 h, with rain peaks exceeding 50 mm/h) between mid-summer and mid-autumn. These frequent extreme weather conditions [37,38] cause flash floods and debris/mud flows [39]. Among the most significant and destructive events in living memory, those of 1915, 1961 and 1995/1996 should be mentioned [40].…”
Section: The Study Areamentioning
confidence: 99%
“…The meteo-climatic features of this area are linked to the cyclogenesis of the Gulf of Genoa [36], which causes events of short but intense precipitation (less than 6 h, with rain peaks exceeding 50 mm/h) between mid-summer and mid-autumn. These frequent extreme weather conditions [37,38] cause flash floods and debris/mud flows [39]. Among the most significant and destructive events in living memory, those of 1915, 1961 and 1995/1996 should be mentioned [40].…”
Section: The Study Areamentioning
confidence: 99%
“…The Mediterranean basin is characterized by its unique climate and hydrological system, making it a region of vital importance for various sectors, including agriculture, water resource management, and ecosystem sustainability [1]. Understanding the trends in hydro-meteorological variables within this area is crucial for assessing the potential impacts of climate change and developing effective adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Petley, 2012 [8], over a period of seven years, recorded 2620 intense landslides worldwide, causing a total of 32,322 fatalities. In addition, a study by Paliaga and Parodi, 2022 [9] showed the increasing trend of extreme events, meteorological variables, and climate-related disasters in the Mediterranean area between 1979 and 2018.…”
Section: Introductionmentioning
confidence: 99%